1986
DOI: 10.1002/cne.902460302
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of GABA‐like immunoreactivity in the brain of the honeybee

Abstract: The distribution of GABA-like immunoreactivity in the brain of the honeybee was investigated with antisera generated against GABA protein conjugates. The binding of the antisera in paraffin serial sections was studied with the peroxidase-antiperoxidase method. GABA-like immunoreactive fibers appeared in all main neuropile areas. The staining of the optic lobes showed pronounced stratification. The receptor cells of compound eyes, ocelli, and antennae were not labelled. Several prominent fiber tracts showed GAB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
144
2
1

Year Published

1996
1996
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 196 publications
(163 citation statements)
references
References 57 publications
16
144
2
1
Order By: Relevance
“…As observed in the honeybee (Schäfer and Bicker, 1986), GABA was distributed differently among the lobula layers in bumblebees in a large number of neurites (Fig. 3C,D).…”
Section: Lobula Layers Contain Different Distributions Of Gaba and Sesupporting
confidence: 69%
See 1 more Smart Citation
“…As observed in the honeybee (Schäfer and Bicker, 1986), GABA was distributed differently among the lobula layers in bumblebees in a large number of neurites (Fig. 3C,D).…”
Section: Lobula Layers Contain Different Distributions Of Gaba and Sesupporting
confidence: 69%
“…3). In past studies, researchers found that lobula layers are evident in honeybee brain tissue immunolabeled for serotonin, octopamine, GABA, and acetylcholinesterase (Schäfer and Bicker, 1986; Kre- D) view, the different layout of GABA (white bands) are combined with the layout of the wide-field layer 1-4 (red), layer 5-6 neurons (blue), and columnar layer 1-6 neurons (green). These neurons predominantly exit the lobula via different tracts, which include the aott, psot, piot, and lot.…”
Section: Distribution Of Neurotransmitters and Neuromodulators In Thementioning
confidence: 99%
“…In subsequent studies, GABAergic LNs have been reported in various insect species (Schäfer and Bicker, 1986;Leitch and Laurent, 1996;Iwano and Kanzaki, 2005;Wilson and Laurent, 2005) and the importance of GABAergic, inhibitory LNs for odor information processing was clearly shown (Stopfer et al, 1997;Sachse and Galizia, 2002;Wilson and Laurent, 2005). In parallel, however, it became increasingly clear that the LNs are a more heterogeneous population of neurons than previously thought.…”
Section: Introductionmentioning
confidence: 92%
“…Historically, LNs have been regarded mostly as GABAergic, inhibitory neurons, and GABAergic LNs have been reported in the AL of various insect species including A. mellifera (Schäfer and Bicker, 1986), Bombyx mori (Iwano and Kanzaki, 2005;Seki and Kanzaki, 2008), D. melanogaster (Wilson and Laurent, 2005), M. sexta (Hoskins et al, 1986), P. americana (Distler, 1989), and S. americana (Leitch and Laurent, 1996). Immunohistochemical, mass-spectrometric and physiological studies, however, showed that the LNs are biochemically a more heterogeneous population of neurons than previously thought.…”
Section: Types Of Local Interneuronsmentioning
confidence: 99%
“…Among the invertebrates, the GABA neurotransmitter has so far been revealed and localized only in insects, molluscs, and nematodes (Bicker et al, 1985;Datum et al, 1986;Hoskins et al, 1986;Meyer et al, 1986;Schafer & Bicker, 1986;Vitellaro et al, 1988;Distler, 1990;Malum, 1991;Richmond et al, 1991;Guastella & Stretton, 1991;Watson & England, 199D. In insects, GA-BA-ir neurone profiles and synapses contain small immunolabelled clear vesicles (25 nm long), while in molluscs the GABA immunoreactivity seems to be present on vesicles of the same size, but of a pleiomorphic shape, such as those with an electron-dense core present in mammalian nervous tissue (Van den Pol, 1986;De Biasi et al, 1986;Vitellaro et al, 1988).…”
Section: Discussionmentioning
confidence: 99%